The Role of Hysteroscopy in the Diagnosis and Treatment of Adenomyosis. (9th August 2017) - Di Spiezio Sardo, Attilio; Calagna, Gloria; Santangelo, Fabrizia; Zizolfi, Brunella; Tanos, Vasilis; Perino, Antonino; De Wilde, Rudy Leon
Abstract : Uterine adenomyosis is a common gynecologic disorder in women of reproductive age, characterized by the presence of ectopic endometrial glands and stroma within the myometrium. Dysmenorrhea, abnormal uterine bleeding, chronic pelvic pain, and deep dyspareunia are common symptoms of this pathological condition. However, adenomyosis is often an incidental finding in specimens obtained from hysterectomy or uterine biopsies. The recent evolution of diagnostic imaging techniques, such as transvaginal sonography, hysterosalpingography, and magnetic resonance imaging, has contributed to improving accuracy in the identification of this pathology. Hysteroscopy offers the advantage of direct visualization of the uterine cavity while giving the option of collecting histological biopsy samples under visual control. Hysteroscopy is not a first-line treatment approach for adenomyosis and it represents a viable option only in selected cases of focal or diffuse "superficial" forms. During office hysteroscopy, it is possible to enucleate superficial focal adenomyomas or to evacuate cystic haemorrhagic lesions of less than 1.5 cm in diameter. Instead, resectoscopic treatment is indicated in cases of superficial adenomyotic nodules > 1.5 cm in size and for diffuse superficial adenomyosis. Finally, endometrial ablation may be performed with the additional removal of the underlying myometrium .